Non-verbal means of communication of young people - Kelmaganbetova, A.; Luchik, M. (KU Publ., 2022)
This article considers the non-verbal means of communication between young people. The authors pay special attention to the characteristics of non-verbal communication, especially the functions and types of nonverbal communication. Non-verbal communication is a means of information, a system of non-verbal symbols, signs used to transmit the message. People can learn a lot about us only by the way we dress, gesticulate, talk, other physical characteristics like hairstyle, home decor, etc. Often, the use of non-verbal communication occurs unconsciously or involuntarily, and those around us learn to understand us based on how they interpret non-verbal communication for themselves. Therefore, in the modern world, non-verbal means of communication are highly valued, their meanings are studied and even how to use them properly is taught. Understanding gestures and facial expressions facilitates mutual understanding of people. It is noteworthy that verbal communication covers only forty percent of the transmitted information. The remaining sixty percent is non-verbal communication, that is, communication using gestures, facial expressions, and posture. The authors came to the conclusion that nonverbal means of communication are as important as linguistic means in the process of communication and carry vast amounts of information.
Жастар арасындағы бейвербалды қарым қатынастар амалдары
Невербальные средства коммуникации молодежи
Keywords: non-verbal means; communication; gesture; facial expressions; signs; verbal communication